Marie Curie more than meets the eye - Mozer, Richard; Trotter, Kate.; Vansier, Natalie; Rennison, Colleen; Greenhalgh, Dawn.; Devine Productions (Toronto, Ont. : Devine Productions, 2002)
A dramatization of the life and times of Marie Curie.
Originally broadcast in 1998 as an HBO original program.
Kate Trotter, Natalie Vansier, Colleen Rennison, Dawn Greenhalgh.
DVD; Dolby Digital stereo.
In English, Spanish or French; closed-captioned.
Keywords: Curie, Marie, -- 1867-1934 -- Drama; Women scientists -- Poland -- Drama; Chemists -- Poland -- Biography -- Drama; Women -- Biography -- Drama; z; z; Serie Mujeres -- v; Made-for-TV movies; Biographical television programs; Video recordings for hard of hearing people